Dissolved inorganic carbon evolution in neutral discharge from mine tailings piles. Issue 13 (3rd February 2016) - Ali, Hendratta N.; Atekwana, Eliot A.
Abstract: We measured the concentrations of dissolved inorganic carbon (DIC) and major ions and the stable carbon isotope ratios of DIC (δ 13 CDIC ) in two creeks discharging from carbonate‐rich sulphide‐containing mine tailings piles. Our aim was to assess downstream carbon evolution of the tailings discharge as it interacted with the atmosphere. The discharge had pH of 6.5–8.1 and was saturated with respect to carbonates. Over the reach of one creek, the DIC concentrations decreased by 1.1 mmol C/l and δ 13 CDIC increased by ~4.0‰ 200 m from the seep source. The decrease in the DIC concentrations was concomitant with decreases in the partial pressure of CO2(aq) because of the loss of excess CO2(aq) from the discharge. The corresponding enrichment in the δ 13 CDIC is because of kinetic isotope fractionation accompanying the loss of CO2(g) . Over the reach of the other creek, there was no significant decrease in the DIC concentrations or notable changes in the δ 13 CDIC . The insignificant change in the DIC concentrations and the δ 13 CDIC is because the first water sample was collected 160 m away from the discharge seep, not accessible during this research. In this case, most of the excess CO2(aq) was lost before our first sampling station. Our results indicate that neutral discharges from tailings piles quickly lose excess CO2(aq) to the atmosphere and the DIC becomes enrich in 13 C. We suggest that a significant amount of carbon cycling in neutral discharges from tailings piles occur close to the locations where the discharge seeps to the surface. Copyright © 2015 John Wiley & Sons, Ltd.